Hypnosis Reconsidered, Resituated, and Redefined - Crabtree, Adam (Journal of Scientific Exploration, 2012)
The two-hundred-year history of hypnosis and its predecessor, animal magnetism, is replete with stories of unusual phenomena. Perhaps surprisingly, a close reading of that history reveals that investigators and students of hypnosis have been unable to achieve an agreed-upon definition of their subject matter. Because of this failure to describe the essential nature of hypnosis, they resorted to lists of hypnotic phenomena as a means for confirming the presence of a hypnotic state in clinical and experimental situations. However, identification and enumeration of hypnotic phenomena proved to be problematic. The content of these lists varied from era to era and from practitioner to practitioner, and the selection of phenomena seemed to be an arbitrary process. With no agreed-upon definition and no definitive list of phenomena that would apply to hypnosis and hypnosis alone, there was no way to ensure that the “hypnosis” that was being studied in clinical and experimental work was the same entity in all cases. Although hypnosis research in recent decades has yielded important insights, significant difficulties and disagreements remain. It is the contention of this article that this confusing state of affairs came to pass because the discussion of hypnosis in the literature was wrongly situated and that there is a need to step back and gain a new perspective on hypnosis and hypnotic phenomena. The proposed fresh look at hypnosis situates hypnosis as a subspecies of trance as defined in a very specific way: a state of profound focus on something accompanied by a diminished awareness of everything else, which evokes appropriate subliminal resources. Hypnosis is then defined as an inner-mind trance characterized by rapport. This new approach and its implications are discussed in some detail. Keywords: hypnosis—trance—rapport